Mass transfer characteristics of yeast fermentation broth in the presence of pluronic F-68 - Elibol, M (Elsevier Sci Ltd, 1999)
A nonionic surfactant, Pluronic F-68, was used to investigate mass transfer characteristics of a fermentation medium in a 11 bench-top bioreactor. At low flow rate (0.08 vvm), k(L)a did not change significantly with increasing agitation speed. In all air flow rates studied, pluronic caused a remarkable reduction in k(L)a. When an oxygen carrier such as perfluorocarbon (PFC) was added to the medium, k(L)a increased with increasing PFC concentration. Moreover, PFC emulsified with pluronic F-68 resulted in a significant increase in k(L)a values. The inclusion of 4 g l(-1) pluronic in yeast fermentation medium resulted in a longer lag phase, while the final biomass concentration was almost unaffected. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: mass transfer; yeast fermentation broth; k(L)a; perfluorocarbon; Pluronic F-68